Representations of memory in the Andean festivities - Robles Mendoza, Roman (2015)
In the villages of southern Ancash, patron saint festivities constitute relevant ceremonial acts of annual cycle social life. These types of holidays were imposed during the colonial period as part of the process of Christianization, as opposed to the beliefs and rituals of pre-Hispanic sacred symbols. To this end, the Spanish instituted in each locality of Indians reduced a saint as an employer to whom they should worship at the Western calendar date. In about five centuries, patron saint festivities in all of Peru are still social and cultural events of great importance and have taken over time special connotations which transcend the space where they perform. In the provinces of Bolognesi and Ocros (southern Ancash), each population has a picture patron, which he provide a party with religious rituals and a complex sequence of social events, with a massive turnout of attendees. The parties are animated by music bands and typical orchestras. Captains and Incas dance in memory of the tragedy of Cajamarca, where the Inca Atahualpa was captured and killed by the Spanish invaders in 1532. The organization of these events is the responsibility of officials, primary and secondary, with specific functions, which are denominated according to the custom of each village. Officials should take high costs to cover the ceremonial requirements of the party. This is where social networks work like familial, communal and amical type to support the realization of a good party. The kinship networks are in operation since the appointment of officials and culminated in his termination. One mechanism Andean reciprocal works in these villages is kelli system. Consists in the provision of services or “donation” of cash resources, with the understanding that this gift will be returned to the offeror in the same equivalence and sense that has been rendered. Without the cooperation of Kellis the parties not have the popular glow that characterize to these people.